Rheb/mTOR/p70s6k Cascade and TFE3 Expression in Conventional and Sclerosing PEComas of the Urinary Tract. Issue 7 (August 2016) - Planelles, María; Macías, Laura; Peiró, Gloria; Bulimbasič, Stela; Hes, Ondrej; Robles, Antonio; Michal, Michal; Davidson, Whitney; López, José I.
Abstract : Perivascular epithelioid cell tumors (PEComas) are rarely found in the urinary tract. The clinicopathologic characteristics of 10 cases, retrospectively collected from 5 medical institutions in 3 different European countries, are presented in this study. Male/female ratio was 3:7 and the average age at diagnosis was 62.7 years. Nine cases were sporadic and 1 showed germline mutation of the TSC2 gene. Eight cases were located in the kidney, 1 in the left adrenal and 1 in the right ureter. All of the patients were alive and free of disease at the time of last contact (mean follow-up, 14.1 mo). Four cases displayed a conventional morphology and 6 showed a prominent sclerotic stroma. By immunohistochemistry, melanocytic markers were consistently expressed, especially HMB-45 (10 cases), MiTF (9 cases), and Melan-A (6 cases). Desmin was expressed in 6 cases; 2 cases were positive for CD117; a single case showed TFE3 expression. pMAPK, mTOR, and pAKT demonstrated variable immunostaining with focal positivity in 7, 4, and 2 cases, respectively. Cytokeratins were repeatedly negative in all cases. PEComas in the urinary tract, especially in the renal region, may show a relatively high frequency of the sclerosing histologic subtype. Knowledge of the distinct histology and immunohistochemical profile is vital to correctly diagnose this rare entity.